Joint space width measures cartilage thickness in osteoarthritis of the knee: high resolution plain film and double contrast macroradiographic investigation. - Buckland-Wright, J C (1995)
OBJECTIVE--To test reliability of joint space width (JSW) measurements as a predictor of cartilage thickness in knees of patients with osteoarthritis (OA), using high definition microfocal radiography. METHOD--JSW was measured from weight bearing plain film macroradiographs taken in the tunnel view and compared with the sum of femoral and tibial cartilage thicknesses measured from double contrast macroarthrograms of the same regions of the same knees obtained in the non-weight bearing lateral position. RESULTS--All knees had medial compartment OA. Comparison of the JSW with the sum of the tibial and femoral cartilage thicknesses revealed a highly significant correlation (p < 0.0001) between the two measurements in the medial but not the lateral compartment. In the middle region of both compartments, JSW was smaller than the cartilage thickness, indicating that, on standing, the curvature of the femoral condyles compressed the cartilage in this region. CONCLUSIONS--JSW reliably measured cartilage thickness in the medial but not the lateral compartment of knees with medial compartment OA. Depending upon the stage of OA disease, JSW reliably reflects cartilage thinning and compression.